A new Mexican species of Rhyparus Westwood (Coleoptera: Scarabaeidae: Aphodiinae), with new records and a key to the Mexican and Guatemalan species - Mora-Aguilar, Eder F.; Delgado, Leonardo (Zootaxa, 2019)
In this paper we describe Rhyparus chimalapensis new species (Coleoptera: Scarabaeidae: Aphodiinae: Rhyparini), from the region of Chimalapas, Oaxaca, Mexico. New records are given for three species of Rhyparus Westwood from Mexico and Guatemala. A key to the Mexican and Guatemalan species of this genus is included.